Tuning Up the Old Brain with New Tricks: Attention Training via Neurofeedback - Jiang, Yang; Abiri, Reza; Zhao, Xiaopeng (Frontiers in Aging Neuroscience, 2017)
Neurofeedback is a form of biofeedback that uses real-time modulation of brain activity to enhance brain function and behavioral performance. Recent advances in Brain-Computer Interfaces (BCI) and cognitive training have provided new tools and evidence that neurofeedback improves cognitive functions, such as attention and working memory, beyond what is provided by traditional cognitive training. More published studies have demonstrated the efficacy of neurofeedback, particularly for treating attention deficit hyperactivity disorder (ADHD) in children. In contrast, there have been fewer studies done in older adults with or without cognitive impairment, with some notable exceptions. The focus of this review is to summarize current success in real-time neurofeedback training of older brains aiming to match those of younger brains during attention/working memory tasks. We also outline potential future advances in real-time brainwave-based neurofeedback for improving attention training in older populations. The rapid growth in wireless recording of brain activity, machine learning classification, and brain network analysis provides new tools for combating cognitive decline and brain aging in older adults. We optimistically conclude that neurofeedback, combined with new neuro-markers (event-related potentials and connectivity) and traditional features, promises to provide new hope for brain and cognitive training in the growing older population.